The persistence of global terrorism - Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
This study investigates persistence of global terrorism in a panel of 163 countries for the period 2010 to 2015. The empirical evidence is based on Generalised Method of Moments. The following findings are established. First, persistence in terrorism is a decreasing function of income levels because it consistently increases from high income (through upper middle income) to lower middle income countries. Second, compared to Christian-oriented countries, terrorism is more persistent in Islam-oriented nations. Third, landlocked countries also reflect a higher level of persistence relative to their coastal counterparts. Fourth, Latin American countries show higher degrees of persistence when compared with Middle East and North African (MENA) countries. Fifth, the main determinants of the underlying persistence are political instability and weapons import. The results are discussed to provide answers to four main questions which directly pertain to the reported findings. These questions centre on why comparative persistence in terrorism is based on income levels, religious orientation, landlockedness and regions.
Keywords: C52; D74; F42; K42; O38; 330; Terrorism; Persistence; Development